Efek antibakteri ekstrak etanol daun sirsak (Annona muricata L.) muda dan tua terhadap Pseudomonas aeruginosa ATCC 9027 - Gede Agung Dhimasena Widyananda; Agung Nova Mahendra; I Made Jawi (DiscoverSys Inc., 2021)
Background: Pseudomonas aeruginosa is an organism that is difficult to handle because it has the ability to resist various antibiotics. Two mechanisms have been studied regarding how Pseudomonas aeruginosa is resistant to both intrinsic and adaptive action of antibiotics. This study aims to determine the antibacterial effect of young and old soursop (Annona muricata L.) leaves ethanol extract against Pseudomonas aeruginosa ATCC 9027.Methods: This study uses the True Experimental Control Group Design method. Samples were divided into 3 groups, namely the control group (K), the intervention group young soursop leaves (EDM) and old soursop leaves (EDT). The control group was divided into negative and positive controls and the intervention group was divided into three groups based on the dosage of using the ethanol extract of Annona muricata L leaves in each isolate with a concentration of 25 mg/mL, 50 mg/mL, and 100 mg/mL, respectively, in group of young and old soursop leaves. Data were analyzed using SPSS version 20 for Windows.Results: The results of the Kruskal-Wallis test showed that there was a significant difference in the inhibition zone in the treatment group, namely the concentration of young and old soursop leaves ethanol extract (25%, 50%, 100%) against the inhibition zone of Pseudomonas aeruginosa bacteria (P <0.05. ).Conclusion: The ethanol extract of young soursop (Annona muricata L.) leaves did not have the effect of inhibiting the growth of Pseudomonas aeruginosa bacteria in vitro. Besides that, the ethanol extract of old soursop (Annona muricata L.) leaves did not have the effect of inhibiting the growth of Pseudomonas aeruginosa bacteria in vitro. Latar Belakang: Pseudomonas aeruginosa merupakan organisme yang sulit untuk ditangani karena memiliki kemampuan resistensi terhadap berbagai antibiotik. Terdapat dua mekanisme yang telah dipelajari mengenai bagaimana Pseudomonas aeruginosa resisten terhadap kerja antibiotik baik intrinsik maupun adaptif. Penelitian ini bertujuan untuk mengetahui efek antibakteri ekstrak etanol daun sirsak (Annona muricata L.) muda dan tua terhadap Pseudomonas aeruginosa ATCC 9027.Metode: Penelitian ini menggunakan metode True Experimental Control Group Design. Sampel dibagi dalam 3 kelompok yakni kelompok kontrol (K), kelompok intervensi daun sirsak muda (EDM) dan daun sirsak tua (EDT). Kelompok kontrol dibagi atas kontrol negatif dan positif serta kelompok intervensi dibagi atas tiga kelompok berdasarkan dosis penggunaan ekstrak etanol daun Annona muricata L. pada masing-masing isolat, dengan konsentrasi 25 mg/mL, 50 mg/mL, dan 100 mg/mL pada masing-masing kelompok daun sirsak muda dan tua. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Hasil uji Kruskal-Wallis yang dapat dilihat menunjukan terdapat perbedaan bermakna zona hambat pada kelompok perlakuan yaitu konsentrasi ekstrak etanol daun sirsak muda dan tua (25%, 50%, 100%) terhadap zona hambat bakteri Pseudomonas aeruginosa (P < 0,05).Kesimpulan: Ekstrak etanol daun sirsak (Annona muricata L.) muda tidak memiliki efek menghambat pertumbuhan bakteri Pseudomonas aeruginosa secara in vitro. Disamping itu, ekstrak etanol daun sirsak (Annona muricata L.) tua tidak memiliki efek menghambat pertumbuhan bakteri Pseudomonas aeruginosa secara in vitro.